PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS MATEMATIS SISWA PADA MATERI POLA BILANGAN DI KELAS VIII SMP NEGERI 5 PEMATANGSIANTAR - Citra Fuji Geovani Tampubolon; Suprapto Manurung; Ropinus Sidabutar (MES: Journal of Mathematics Education and Science, 2022)
This study aims to determine the effect of the discovery learning model on students' mathematical critical thinking skills. This study uses the Quasy experimental method with a Nonequivalent Control Group Design. Sampling was carried out using the Purpose sampling technique so that students from classes VIII-2 and VIII-3 were selected as the control class and 32 people from the experimental class were selected. The instrument used in the form of an essay test of 5 items that have been declared worthy. Both samples have met the test data requirements and are declared to meet the requirements of normality and homogeneity. Furthermore, to test the hypothesis using the T-Test, the results show that there is an influence of the discovery learning model on students' mathematical critical thinking skills on number pattern material in class VIII of SMP Negeri 5 Pematangsiantar